Interactions II - Tanka, Judith (Nxb. Tp. Hồ Chí Minh, 1997)
Interactions Mosaic 4th Edition is the newly expanded five-level, four-skill comprehensive ESL/ELT series for academic students. The new edition, for beginners to advanced learners, incorporates interactive and communicative activities while still focusing on skill building to prepare students for academic content.